PENGARUH JUMLAH AJIR DAN JUMLAH DAUN PADA AJIR TERHADAP PERTUMBUHAN TUNAS DAN SAAT MANJING PETIK PERTAMA PADA PEMANGKASAN AJIR TANAMAN TEH (Camellia sinensis L.) DI DATARAN TINGGI - Ade Wachjar; , Supijatno; Riswan Basyri Nasution (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
The experiment was aimed to study the effect of number of lungs and leaves at lung to growth of shoots and first time harvest at lung pruning of height land tea (Camellia sinensis). The experiment carried out at Gedeh Tea Plantation, PTPN XII, Cianjur, West Java, from December 1993 to March 1994. In this case we used tea Clone TRI 2025. The experiment was arranged in Randomized Block Design with 3 replications. The first factor, number of lungs, consisted of 3 different level : 2, 3, 4 lungs per tea. The second factor, number of leaves at lung, consisted of 3 different levels : 25, 50, and 75 leaves per lung. The Experiment showed that number of shoots and first time harvest affected by number of lungs, but number of lungs didn't affect to height of shoot, percentage of banji, wet weight shoots on tipping and first pluck production were not affected. The tea with 4 lungs had significantly greater number of shoots than 2 or 3 lungs. The earliest first harvest time was achieved by 2 lungs tea (3 to 9 days earlier), but was significant with 3 lungs tea.